Esports players, got muscle? Competitive video game players' physical activity, body fat, bone mineral content, and muscle mass in comparison to matched controls - Joanne DiFrancisco-Donoghue; William G. Werner; Peter C. Douris; Hallie Zwibel (Elsevier, 2022)
Background: Esports players, like traditional athletes, practice for long hours and, thus, are vulnerable to the negative health effects of prolonged sitting. There is a lack of research on the physical activity and the health ramifications of prolonged sitting by competitive players. The purpose of this study was to investigate activity levels, body mass index (BMI), and body composition in collegiate esports players as compared to age-matched controls. Methods: Twenty-four male collegiate esports players and non-esports players between 18 and 25 years of age signed a written consent to participate. Physical activity was examined using daily activity (step count) with a wrist-worn activity tracker. A questionnaire assessing physical activity was also administered. Secondary outcomes included body-fat percentage, lean-body mass, BMI, and bone mineral content measured using dual X-ray absorptiometry. Results: The step count in the esports players was significantly lower than the age-matched controls (6040.2 ± 3028.6 vs. 12843.8 ± 5661.1; p = 0.004). Esports players exhibited greater body-fat percentage (p = 0.05), less lean body mass (p = 0.003), and less bone mineral content (p = 0.03), despite no difference in BMI between the esports and non-esports players. Conclusion: As compared to non-esports players, collegiate esports players were significantly less active and had a higher body-fat percentage, with lower lean body mass and bone mineral content. The BMIs showed no difference between the 2 groups. Esports athletes displayed significantly less activity and poor body composition, which are all correlated with potential health issues and risk of injury. BMI did not capture this difference and should not be considered as an accurate measure of health in competitive esports players.